1984
DOI: 10.2320/matertrans1960.25.43
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Parameter, <I>P</I><SUB>\ominus</SUB>, for the Determinations of Mixed Ionic and N-Type Electronic Conduction in Commercial Zirconia Electrolytes

Abstract: Coulometric titration technique has been employed for the determination of the parameter, Pe, defined as the oxygen partial pressure at which the n-type and ionic conductivities are equal, for various commercial zirconia electrolytes in the temperature range from 1243 to 1873 K. Measured values of the parameter, P, have been expressed by a formula, logP=A+B/T, where A and B denote constants. The P values for CaO-stabilized ZrO2 have shown negligible dependence on the conMeasured values of P for MgO-stabilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…[24][25][26][27][28] calculated using the modified Nernst equation (Eq. [1]) and Generally, P is considered as a function of temperature and the EMF reading from the oxygen concentration cell as the composition of the electrolyte.…”
Section: The Basic Principle Of Feo Activity Measurementmentioning
confidence: 99%
“…[24][25][26][27][28] calculated using the modified Nernst equation (Eq. [1]) and Generally, P is considered as a function of temperature and the EMF reading from the oxygen concentration cell as the composition of the electrolyte.…”
Section: The Basic Principle Of Feo Activity Measurementmentioning
confidence: 99%
“…The parameter P for stabilized zirconia electrolytes produced by Nippon Kagaku Togyo Co. Ltd. were measured by Iwase et al (12). The result for 0.91ZrO2+0.09MgO…”
Section: Activity Of Chromium and Nickel In The Liquid Ni-cr Alloysmentioning
confidence: 99%
“…Values for this parameter for the magnesia-stabilized zirconia tubes used in this study have been reported elsewhere. 12) logðP e =PaÞ ¼ 2:54 Â 10 À 6:45 Â 10 4 =ðT=KÞ ð3Þ…”
Section: Resultsmentioning
confidence: 99%